Longitudinal Estimates of the Union Effects on Wages, Wage Dispersion and Pension Fringe Benefits - Swidinsky, R.; Kupferschmidt, M. (Relations industrielles / Industrial Relations, 1991)
This study provides evidence of the union effect on wages, wage dispersion and pension fringe benefits derived entirely from the new Canadian longitudinal micro data base.